Le Rôle De La Responsabilité Sociale Des Entreprises Dans La Gestion Des Risques Psychosociaux: Cas De L’agence Nationale Des Ports - Tourabi, Amina (European Scientific Journal, ESJ, 2016)
Understood as a key theme in management literature, social responsibility (CSR) is installed between two frames reflections namely business ethics and sustainable development. Several researchers have invested in the issue of CSR but few who have reconciled with the risk management and prevention modalities. By analyzing the social contribution of CSR, our goal is to highlight the emerging relationship between CSR and management of psychosocial risks (RPS), formulating the following questions: can we reconcile CSR as a tool RPS management? What is the contribution of CSR to PR management issues? What is the effect of CSR on factors psychosocial risks? Based on the theoretical foundations of CSR, we propose to cross the methodology and action of CSR in RPS generators factors while controlling the level of well-being at work. By analyzing the perception of the employees of the CSR approach, we presented the maturity level of CSR through the materiality test, then we evaluated the social aspect of the approach through the score method to finally study the differences between the criticality PHI before and after the CSR deployment in port activity